PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA DIMEDIASI KINERJA GURU (Studi pada Guru Sekolah Dasar di UPT Dindikbud Doro Kabupaten Pekalongan) - Romadi, 13.5202.0117 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aims to examine and analyze the influence of motivation and organizationalcommitment to job satisfaction mediated UPT performance of teachers in the Departmentof Education and Culture Doro Pekalongan. The population in this study were allprimary school teacher (SD) in the Department of Education and Culture Unit DoroPekalongan as much as 219 people. Sampling this study using a sampling techniqueproportional sampling is a way of sampling by selecting each sampling unit inaccordance with the size of the sampling unit so that the study sample is 142 people.Hypothesis testing is done by using the direct hypothesis testing and test mediation. Theresults showed that motivation significant and positive impact on teacher performance,organizational commitment significant and positive impact on teacher performance,motivation significant and positive impact on job satisfaction, organizational commitmentsignificant and positive impact on job satisfaction, teacher performance significant andpositive impact on satisfaction work, the performance of teachers do not mediate theeffect of motivation on job satisfaction, teacher performance does not mediate the effectof organizational commitment on job satisfaction.Keywords: motivation, organizational commitment, teacher performance, job satisfaction